The Effect of Benson Relaxation and Dhikr on Decreasing Pain Scale in Active Phase I Delivery Mothers at Yosi Trihana Independent Midwifery Practice - Shella Novitasari; Sulastri Sulastri (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Pain management uses pharmacological and non-pharmacological approaches, to reduce pain by treating accompanying symptoms. One of the non-pharmacological pain treatments is Benson relaxation therapy and dhikr. Benson relaxation therapy is a non-pharmacological strategy that combines relaxation techniques with the patient's belief system. It aims to reduce pain and encourage calmness by focusing on Allah SWT and releasing all emotions to the mother. The purpose of this study was to determine the effect of Benson relaxation and dhikr on reducing the pain scale in mothers inpartu kala I active phase. The research method used is quantitative with a pre-experimental research design, with the type of research one group pre-post test. The research location was at the Yosi Trihana Independent Practice Midwife, Klaten Regency, Central Java. They were carried out in November 2023 to January 2024. The population used was all active mothers inpartu active phase I. The sampling technique was total sampling, so the research sample was 30 respondents. The research instrument used the Numeric Rating Scale (NRS) pain scale. Data analysis was performed using the Wilcoxon test, which was processed using SPSS software version 20.0. The results showed a significant relationship with a p-value = (0.000). There is a decrease in the intensity of pain experienced during the labour process in Yosi Trihana's Independent Midwife Practice. These findings indicate that benzene relaxation and dhikr significantly impact reducing pain levels during labour. It is recommended that nurses and other health workers use dhikr relaxation as a non-pharmacological technique to reduce pain during labour. Keywords: Benson Relaxation, Dhikr, Pain Intensity Scal